Dosimetric impact of source-positioning uncertainty in high-dose-rate balloon brachytherapy of breast cancer - Kim, Yongbok (Journal of Contemporary Brachytherapy, 2015)
Purpose: To evaluate the dosimetric impact of source-positioning uncertainty in high-dose-rate (HDR) balloon brachytherapy of breast cancer. Material and methods : For 49 HDR balloon patients, each dwell position of catheter(s) was manually shifted distally (+) and proximally (–) with a magnitude from 1 to 4 mm. Total 392 plans were retrospectively generated and compared to corresponding clinical plans using 7 dosimetric parameters: dose (D 95 ) to 95% of planning target volume for evaluation (PTV_EVAL), and volume covered by 100% and 90% of the prescribed dose (PD) (V 100 and V 90 ); skin and rib maximum point dose (D max ); normal breast tissue volume receiving 150% and 200% of PD (V 150 and V 200 ). Results: PTV_EVAL dosimetry deteriorated with larger average/maximum reduction (from ± 1 mm to ± 4 mm) for larger source position uncertainty (p value < 0.0001): from 1.0%/2.5%, 3.3%/5.9%, 6.3%/10.0% to 9.8%/14.5% for D 95 ; from 1.0%/2.6%, 3.1%/5.7%, 5.8%/8.9% to 8.7%/12.3% for V 100 ; from 0.2%/1.5%, 1.0%/4.0%, 2.7%/6.8% to 5.1%/10.3% for V 90 . ≥ ± 3 mm shift reduced average D 95 to < 95% and average V 100 to < 90%. While skin and rib D max change was case-specific, its absolute change (|Δ(Value)|) showed that larger shift and high dose group had larger variation compared to smaller and lower dose group (p value < 0.0001), respectively. Normal breast tissue V 150 variation was case-specific and small. Average |Δ(V 150 )| was 0.2 cc for the largest shift (± 4 mm) with maximum < 1.7 cc. V 200 was increased with higher elevation for larger shift: from 6.4 cc/9.8 cc, 7.0 cc/10.1 cc, 8.0 cc/11.3 cc to 9.2 cc/13.0 cc. Conclusions : The tolerance of ± 2 mm recommended by AAPM TG 56 is clinically acceptable in most clinical cases. However, special attention should be paid to a case where both skin and rib are located proximally to balloon, and the orientation of balloon catheter(s) is vertical to these critical structures. In this case, sufficient dosimetric planning margins are required.